Nonwoven fabric, absorbent article including the nonwoven fabric and manufacturing method of the nonwoven fabric
The nonwoven fabric with thermoplastic resin and specific manufacturing processes addresses the challenges of bulkiness, breaking strength, and slitting properties in absorbent articles, resulting in a high-performance fabric for use in disposable diapers and similar products.
Patent Information
- Application Number
- JP2023169772
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-29
- Publication Date
- 2025-04-10
AI Technical Summary
The existing nonwoven fabrics used in absorbent articles, such as disposable diapers and sanitary napkins, face issues with bulkiness, breaking strength, and slitting properties, particularly during the slitting process where cut ends can be disturbed.
A nonwoven fabric is developed with thermoplastic resin, featuring embossed and non-embossed portions where fiber intersections melt and adhere, resulting in high bulkiness, breaking strength, and improved slitting properties. The fabric is manufactured using a process involving hot air through treatment, thermal embossing, and a second hot air through treatment.
The resulting nonwoven fabric exhibits enhanced bulkiness, breaking strength, and excellent slitting properties, making it suitable for use in absorbent articles such as disposable diapers, sanitary napkins, or incontinence pads.
Smart Images

Figure 2025059595000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a nonwoven fabric, an absorbent article comprising the nonwoven fabric, and a method for making the nonwoven fabric. [Background technology]
[0002] In recent years, the performance requirements for absorbent articles, such as sanitary materials, including disposable diapers, sanitary napkins, incontinence pads, etc., have become more stringent. In particular, in the composition of disposable diapers, the top sheet that comes into contact with the skin and the back sheet, which must be comfortable to the touch, are required to have high flexibility and bulkiness that provides cushioning, and in the case of adult diapers, which may involve nursing care, high breaking strength is required.
[0003] The following Patent Document 1 describes a method for producing a bulky nonwoven fabric having cushioning softness suitable for top sheets and back sheets of absorbent articles used as sanitary materials, by fusing a long-fiber nonwoven fabric using an air-through method with hot air. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Special table 2023-508805 publication Summary of the Invention [Problem to be solved by the invention]
[0005] However, the nonwoven fabric described in Patent Document 1 is bonded only by the air-through method using hot air, which causes a problem in that the cut ends become irregular during the slitting process (i.e., the process of cutting the nonwoven fabric roll to the required width) in the nonwoven fabric manufacturing process.
[0006] In view of the above problems, the problem that the present invention aims to solve is to provide a nonwoven fabric that has high bulkiness and breaking strength and also has good slittability, an absorbent article containing the nonwoven fabric, and a method for producing the nonwoven fabric. [Means for solving the problem]
[0007] As a result of intensive research and repeated experiments to solve the above problems, the inventors of the present application unexpectedly discovered that the problems could be solved by adopting the following configuration, and thus completed the present invention. That is, the present invention is as follows. [1] A nonwoven fabric containing a thermoplastic resin, which has embossed and non-embossed parts, in which the intersections of fibers in the non-embossed parts are melted and bonded, and the value of the warp tear strength of the nonwoven fabric divided by the basis weight is 0.4 N / (g / m 2 ) or less, and the bulk density of the nonwoven fabric is 0.02 g / cm 3 More than 0.09g / cm 3 A nonwoven fabric, characterized in that: [2] The nonwoven fabric according to [1], wherein the thermoplastic resin is a polyolefin. [3] The nonwoven fabric according to [1] or [2], wherein the thermoplastic resin is only polypropylene or polyethylene. [4] The nonwoven fabric according to [1] or [2], wherein the thermoplastic resin comprises a composite fiber of polypropylene and polyethylene. [5] The nonwoven fabric according to [4], wherein the composite fiber is a side-by-side type, a sheath-core type, or an eccentric-core-sheath type fiber. [6] The nonwoven fabric according to any one of [1] to [5] above, which is a long-fiber nonwoven fabric. [7] An absorbent article comprising the nonwoven fabric according to any one of [1] to [6] above. [8] The absorbent article according to [7] above, which is a disposable diaper, a sanitary napkin or an incontinence pad. [9] The following steps: First hot air through treatment process; Hot embossing process; and Second hot air through treatment process; The method for producing a nonwoven fabric according to any one of the above [1] to [6], comprising the steps of: Effect of the Invention
[0008] The nonwoven fabric according to the present invention has high bulkiness and breaking strength, and also has good slittability, and therefore can be suitably used as a component of absorbent articles such as disposable diapers, sanitary napkins, and incontinence pads. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] Hereinafter, embodiments of the present invention (also referred to as the present embodiment in this disclosure) will be described in detail, but the present invention is not limited to these embodiments.
[0010] One embodiment of the present invention is a nonwoven fabric containing a thermoplastic resin, which has embossed and non-embossed portions, in which the intersections of fibers in the non-embossed portions are melted and bonded, and the value of the warp tear strength of the nonwoven fabric divided by the basis weight is 0.4 N / (g / m 2 ) is a nonwoven fabric characterized in that
[0011] The nonwoven fabric of this embodiment may be a long-fiber nonwoven fabric produced by a spunbonding method or the like, or a short-fiber nonwoven fabric produced by a carding method or a wet papermaking method. However, from the viewpoints of strength, productivity, and reduced irritation to the skin, a long-fiber nonwoven fabric is preferred. In this specification, the term "long-fiber nonwoven fabric" refers to a nonwoven fabric defined in JIS-L-0222. The fiber length of the long fibers may be, for example, 55 mm or more.
[0012] The nonwoven fabric of the present embodiment contains a thermoplastic resin. Examples of the thermoplastic resin include polyolefins such as polyethylene, polypropylene, or copolymers of ethylene and / or propylene with other olefins; polyester-based resins such as polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, and copolymerized polyesters; polyamide-based resins such as nylon-6, nylon-66, and copolymerized nylons; and biodegradable resins such as polylactic acid, polybutylene succinate, and polyethylene succinate. The thermoplastic resin may be produced from petroleum as a raw material, or may be produced from biomass raw materials. These thermoplastic resins may be used alone or in combination of two or more types. From the viewpoint of texture, it is preferable to use polyolefins. For example, fibers made of resins such as polyethylene, polypropylene, or copolymers of monomers thereof with other α-olefins may be used. Other α-olefins may have 3 to 10 carbon atoms, and specifically, propylene, 1-butene, 1-pentene, 1-hexane, 4-methyl-1-pentene, 1-octene, etc.
[0013] Among polyolefins, polypropylene is preferred because it has high breaking strength, is unlikely to break during use, and has excellent dimensional stability during the production of sanitary materials. The polypropylene may be a polymer synthesized by a general Ziegler-Natta catalyst, may be a polymer synthesized by a single-site active catalyst such as metallocene, or may be ethylene random copolymer polypropylene. These may be used alone or in combination of two or more. In particular, from the viewpoints of texture, breaking strength, and dimensional stability, it is preferable to use a polymer mainly composed of homopolypropylene. In addition, polyethylene has strong adhesive strength after bonding between fibers and has a good texture as a nonwoven fabric, so it can be suitably used for sanitary materials. The polyethylene may be a polymer synthesized by a general Ziegler-Natta catalyst, or may be a polymer synthesized by a single-site active catalyst such as metallocene. The polyethylene may be high-density polyethylene, linear low-density polyethylene, or low-density polyethylene. These may be used alone or in combination of two or more. In particular, from the viewpoints of texture, breaking strength, and productivity, it is preferable to use a polymer mainly composed of high-density polyethylene or linear low-density polyethylene.
[0014] The MFR (melt mass flow rate) of the thermoplastic resin is preferably 5 g / 10 min to 150 g / 10 min, more preferably 5 g / 10 min to 100 g / 10 min, even more preferably 10 g / 10 min to 85 g / 10 min, particularly preferably 15 g / 10 min to 70 g / 10 min, and most preferably 20 g / 10 min to 65 g / 10 min. The method for measuring the MFR will be described later.
[0015] When the nonwoven fabric of the present embodiment contains only one type of thermoplastic resin, the thermoplastic resin is preferably polypropylene or polyethylene from the viewpoint of texture.
[0016] The nonwoven fabric of this embodiment may contain fibers having a modified cross section or composite fibers combining two or more thermoplastic resins in order to achieve bulkiness. The fiber shape of the composite fiber is not particularly limited, but is preferably a side-by-side type (S / S), eccentric sheath-core type (eccentric S / C) or sheath-core type (S / C). The mass ratio of one of the resins in the fiber is preferably 10% by mass or more and 90% by mass or less, more preferably 20% by mass or more and 80% by mass or less, and even more preferably 30% by mass or more and 70% by mass or less.
[0017] When the composite fiber is made of two kinds of thermoplastic resins, the thermoplastic resin is preferably polypropylene and / or polyethylene, for example, a polypropylene-polyethylene composite fiber. When the composite fiber is an eccentric sheath-core type or a sheath-core type, it is preferable that the core is polypropylene and the sheath is polyethylene.
[0018] The nonwoven fabric of this embodiment has an embossed portion and a non-embossed portion, and the intersections of the fibers are fused and bonded in the non-embossed portion. The "embossed portion" refers to a portion where the nonwoven fabric is partially heat-pressed to form a thin film, and the "non-embossed portion" refers to a portion other than the embossed portion. In addition, in the nonwoven fabric of this embodiment, the intersections of the fibers are fused and bonded in the non-embossed portion. "The intersections of the fibers are fused and bonded" refers to a state where the fibers constituting the nonwoven fabric are not simply abutted but are fused and integrated, and does not include a state where the fibers are bonded by pressure bonding as in the embossed portion. The nonwoven fabric of this embodiment has a non-embossed portion where the intersections of the fibers are fused and bonded, thereby increasing the bulkiness, and the slittability (tearability) is increased from the embossed portion, so that both bulkiness and slittability can be achieved.
[0019] From the viewpoint of good slittability and bulkiness, the area ratio of the embossed portion to the nonwoven fabric area is preferably 3% to 40%, more preferably 4% to 25%, particularly preferably 4% to 20%, and most preferably 5% to 15%. The deeper the embossing, the more bulky the nonwoven fabric can be obtained, and is preferably 0.5 mm to 3.0 mm, more preferably 0.6 mm to 2.5 mm, and even more preferably 0.7 mm to 2.0 mm. The shape of the embossing is not particularly limited, but is preferably a circle, an ellipse, a diamond, or a rectangle. These values are measured by a method of analyzing an image of the nonwoven fabric magnified and photographed with a microscope.
[0020] The tear strength in the warp direction of the nonwoven fabric of this embodiment divided by the basis weight is 0.05 N / (g / m 2 ) or more 0.4N / (g / m 2 ) or less, and more preferably 0.07 N / (g / m 2 ) or more 0.35N / (g / m 2 ) or less, more preferably 0.09 N / (g / m 2 ) or more 0.3N / (g / m 2 ) or less. The longitudinal tear strength is 0.05N / (g / m 2 ) or more, the nonwoven fabric is less likely to break when used as a sanitary material, and is 0.4N / (g / m 2 The slitting property is good when the tear strength is not more than 100%. The method for measuring the tear strength will be described later.
[0021] The nonwoven fabric of this embodiment may have a concave-convex pattern by shaping processing to obtain good flexibility. Unlike the embossed portion, such a concave-convex pattern is formed by deformation of the fibers such as buckling, rather than thinning the fibers by thermocompression. The concave-convex pattern may be a straight line, a curve, an angle, a circle, a matte finish, or other continuous or discontinuous pattern, but a tortoiseshell pattern is preferable to improve bending flexibility in both the vertical direction (MD direction) and the horizontal direction (CD direction). From the viewpoint of flexibility, the depth of the concave or convex portion (the maximum difference between the concave and convex portions) is preferably 0.1 mm or more and 5.0 mm or less, more preferably 0.2 mm or more and 3.0 mm or less, and the greater the depth of the concave or convex portion, the greater the effect. In addition, the area ratio of the concaves (pressing portions) of the concaves and convex portions to the nonwoven fabric area is preferably 5% or more and 40% or less, more preferably 5% or more and 25% or less, in order to obtain good flexibility and touch. The above maximum difference between the concave portions and the convex portions, and the area ratio of the concave portions are values measured by a method of analyzing an image of the nonwoven fabric magnified and photographed with a microscope.
[0022] The nonwoven fabric of the present embodiment may contain a hydrophilizing agent. As such a hydrophilizing agent, nonionic surfactants obtained by adding ethylene oxide to higher alcohols, higher fatty acids, alkylphenols, etc., anionic surfactants such as alkyl phosphates and alkyl sulfates, etc., are preferably used alone or in combination, taking into consideration safety to the human body and safety during the process.
[0023] The content of the hydrophilizing agent varies depending on the performance required of the nonwoven fabric, but is usually preferably in the range of 0.1% to 1.0% by mass, more preferably 0.15% to 0.8% by mass, and even more preferably 0.2% to 0.6% by mass, based on the total mass of the fibers. When the content of the hydrophilizing agent is 0.1% to 1.0% by mass, the nonwoven fabric can have excellent hydrophilic properties and processability, which are particularly suitable for the top sheet of a sanitary material.
[0024] The nonwoven fabric of the present embodiment may contain a lubricant. As such a lubricant, fatty acid amides, fatty acid esters, etc. are preferably used alone or in combination, taking into consideration safety to the human body, etc.
[0025] The content of the lubricant varies depending on the performance required for the nonwoven fabric and the type of lubricant used, but when a fatty acid amide is used as the lubricant, the amount is preferably 0.1% by mass or more and 1.5% by mass or less, more preferably 0.15% by mass or more and 1.0% by mass or less, and particularly preferably 0.2% by mass or more and 0.6% by mass or less, based on the total mass of the fibers. Specific examples of suitable fatty acid amides include lauric acid amide, myristic acid amide, palmitic acid amide, stearic acid amide, behenic acid amide, oleic acid amide, and erucic acid amide, and erucic acid amide is particularly preferred. These fatty acid amides can also be used in combination.
[0026] The method of incorporating the lubricant into the fiber is preferably a polymer blending method, which is easy to mix the lubricant uniformly into the fiber. In addition, in the case of a composite fiber made of two or more resins, the lubricant may be incorporated into the entire fiber or into any one of the resins.
[0027] Furthermore, the nonwoven fabric of this embodiment may contain a nucleating agent, a flame retardant, an inorganic filler, a pigment, a colorant, a heat stabilizer, an antistatic agent, and the like.
[0028] The average single fiber fineness of the fibers constituting the nonwoven fabric of this embodiment is preferably 0.5 dtex or more and 10.0 dtex or less, more preferably 0.7 dtex or more and 8.0 dtex or less, and even more preferably 0.9 dtex or more and 5.0 dtex or less. From the viewpoint of spinning stability, the average single fiber fineness is preferably 0.5 dtex or more, and from the viewpoint of the texture of the nonwoven fabric used for sanitary materials, it is preferably 10.0 dtex or less. The method for measuring the average single fiber fineness will be described later.
[0029] The basis weight of the nonwoven fabric of this embodiment is 8 g / m 2 More than 80g / m 2Preferably less than 10 g / m 2 More than 40g / m 2 More preferably, 10 g / m 2 More than 30g / m 2 Less than 8g / m 2 If it is more than 80g / m, it satisfies the strength requirement for nonwoven fabrics used in sanitary materials. 2 If the nonwoven fabric has a surface area of 100 mm or less, it satisfies the flexibility of the nonwoven fabric used in sanitary materials and does not give the appearance of being thick. The method for measuring the surface area will be described later.
[0030] The bulk density of the nonwoven fabric of this embodiment is 0.02 g / cm 3 More than 0.09g / cm 3 or less, preferably 0.03 g / cm 3 More than 0.08g / cm 3 Less than or equal to 0.04 g / cm 3 More than 0.07g / cm 3 Less than 0.09g / cm 3 If it is less than 0.02 g / cm, the bulkiness is satisfied. 3 If the density is equal to or greater than this, the product will not give an impression of being thick in appearance. The method for measuring the bulk density will be described later.
[0031] In one embodiment, the bending stiffness of the nonwoven fabric may be preferably 50 mm or less, or 45 mm or less, or 40 mm or less. If the bending stiffness is 50 mm or less, a comfortable texture that is particularly suitable for nonwoven fabrics for sanitary materials can be obtained. From the viewpoint of ease of production of the nonwoven fabric, in one embodiment, the bending stiffness may be 10 mm or more, or 15 mm or more, or 20 mm or more. The method for measuring the bending stiffness will be described later.
[0032] The breaking strength of the nonwoven fabric of this embodiment is preferably 15 N / 5 cm or more and 60 N / 5 cm or less, more preferably 20 N / 5 cm or more and 60 N / 5 cm or less, and even more preferably 25 N / 5 cm or more and 60 N / 5 cm or less, on average in the warp direction. If the breaking strength is 15 N / 5 cm or more, the nonwoven fabric is less likely to break when used as a sanitary material, which is preferable. The method for measuring the breaking strength will be described later.
[0033] The nonwoven fabric of this embodiment can be produced by a known method such as a spunbonding method, and may include, for example, a process including: (1) spinning a molten resin; (2) collecting the spun fibers on a moving collecting surface to form a web; (3) bonding the web; may include:
[0034] In the step (1), a thermoplastic resin is extruded from an extruder, and a resin filament is discharged from a spinneret having a large number of spinning holes. When a nonwoven fabric is produced using a composite fiber in which two or more thermoplastic resins are combined, for example, different thermoplastic resins are extruded from two or more different extruders, and the two or more thermoplastic resins can be discharged from the spinneret in a composite state as a resin filament. Air having a temperature controlled to preferably 3 to 28°C is blown onto the discharged resin filament to promote cooling, and a fiber is produced. In the process of producing the fiber, the resin filament may be drawn by a drawing device while being cooled.
[0035] In the step (2), the fibers are deposited on a moving collecting surface to form a web. Another web may be laminated on the web deposited on the conveyor, or a web may be joined and then laminated on another web online or offline. When laminating, each layer may be formed of webs having different fiber diameters, or webs of different fiber configurations (e.g., fibers with a circular cross section, fibers with an irregular cross section, crimped fibers, hollow fibers, etc.) may be laminated.
[0036] The step (3) is a step of bonding the web by heat or the like while transporting it on a moving collecting surface, and it is preferable that this step includes a first hot air air-through processing step, a heat embossing processing step, and a second hot air air-through processing step in this order.
[0037] Another embodiment of the present invention is a method for producing a method for manufacturing a semiconductor device comprising the steps of: First hot air through treatment process; Hot embossing process; and Second hot air through treatment process; The method for producing the nonwoven fabric includes the steps of:
[0038] The first hot air air-through treatment expresses the latent crimp of the fibers, imparting bulkiness and flexibility, followed by heat embossing to improve slittability, and finally the second hot air air-through treatment fuses and fixes the intersections of the fibers in the non-embossed areas, thereby imparting sufficient breaking strength for use as a sanitary material while maintaining bulkiness.
[0039] The temperature of the hot air in the first and second hot air air-through treatments is preferably adjusted to a temperature suitable for the thermoplastic resin that has a low melting point and contributes to bonding among the combined thermoplastic resins. Specifically, the temperature of the hot air is preferably −30° C. or more and +30° C. or less with respect to the melting point of the thermoplastic resin, more preferably −20° C. or more and +20° C. or less, and even more preferably −10° C. or more and +10° C. or less. If the temperature of the hot air is within this range, adhesion between the fibers occurs at the intersections between the fibers, and the breaking strength of the nonwoven fabric can be improved.
[0040] The hot air velocity in the first and second hot air through treatments is preferably 0.5 m / s to 4.0 m / s, more preferably 0.7 m / s to 3.0 m / s, and even more preferably 0.9 m / s to 2.5 m / s. If the hot air velocity is within this range, it is possible to improve the breaking strength while maintaining the bulkiness of the nonwoven fabric.
[0041] From the viewpoint of productivity, the thermal embossing is preferably carried out by passing the sheet through a pair of rolls consisting of a metal embossing roll and a metal flat roll.
[0042] The temperature of the embossing roll is preferably adjusted to a temperature suitable for the thermoplastic resin that has a low melting point and contributes to bonding among the combined thermoplastic resins. Specifically, the temperature of the embossing roll is preferably -30°C or more and +30°C or less relative to the melting point of the thermoplastic resin, more preferably -20°C or more and +20°C or less, and even more preferably -10°C or more and +10°C or less. The time for applying heat to the nonwoven fabric by the embossing roll is preferably 0.1 ms or more and 5 ms or less, more preferably 0.15 ms or more and 3 ms or less, and even more preferably 0.2 ms or more and 2 ms or less. If the time for applying heat to the nonwoven fabric by the embossing roll is within this range, it is possible to develop breaking strength while maintaining the bulkiness of the nonwoven fabric.
[0043] When applying a hydrophilizing agent to the nonwoven fabric of this embodiment, the application method can usually employ an existing method such as a dipping method, a spraying method, or a coating method (with a kiss coater, a gravure coater, or the like) using a diluted hydrophilizing agent. It is preferable to apply the hydrophilizing agent by diluting the hydrophilizing agent, if necessary, with a solvent such as water, which has been mixed in advance.
[0044] When the hydrophilizing agent is diluted with a solvent such as water and then applied, a drying step may be required. In this case, a known method utilizing convection heat transfer, conduction heat transfer, radiation heat transfer, etc., can be used as the drying method, and drying methods using hot air or infrared rays, drying by thermal contact, etc. can be used.
[0045] The nonwoven fabric of this embodiment can be cut to a desired width during the slitting process and then wound up as a product. The method of cutting the nonwoven fabric is not particularly limited, but a method of pressing a round blade cutter against the running nonwoven fabric is preferred. The pressing pressure of the cutter is preferably 0.02 MPa or more and 0.6 MPa or less, more preferably 0.05 MPa or more and 0.5 MPa or less, and even more preferably 0.08 MPa or more and 0.4 MPa or less, and the tension applied to the running nonwoven fabric is preferably 10 N / m or more and 80 N / m or less, more preferably 20 N / m or more and 75 N / m or less, and even more preferably 30 N / m or more and 70 N / m or less. If the pressing pressure of the cutter and the tension of the nonwoven fabric are within the above range, the nonwoven fabric edge can be cut straight without being disturbed.
[0046] Yet another embodiment of the present invention is an absorbent article comprising the nonwoven fabric described above. In one aspect, the absorbent article is a sanitary material for absorbing urine, splashed liquid, etc. The nonwoven fabric of this embodiment has a bulkiness with a cushioning softness, and therefore can be suitably used in the manufacture of sanitary materials, such as disposable diapers, sanitary napkins, and incontinence pads, and can be suitably used for the top sheet and outer back sheet of these sanitary materials.
[0047] The nonwoven fabric of the present embodiment is not limited to the above-mentioned uses, and can also be used for, for example, masks, hand warmers, tape bases, waterproof sheet bases, patch bases, first aid bandage bases, packaging materials, wipe products, medical gowns, bandages, clothing, skin care sheets, and the like. EXAMPLES
[0048] The present invention will be described in detail below with reference to examples and comparative examples, but the present invention is not limited to the following examples. The methods for evaluating each characteristic were as follows.
[0049] (1) Average single yarn fineness (dtex) Excluding 10 cm at both ends of the width of the nonwoven fabric, the fabric was divided into approximately 5 equal parts in the width direction to sample 1 cm square test pieces. The fiber diameter was measured at 20 points on each side using an optical microscope (Keyence Corporation: VHX-8000) and the fineness was calculated from the average value.
[0050] (2) Weight (g / m 2 ) In accordance with JIS-L1906, five test pieces measuring 20 cm in MD × 5 cm in TD were randomly taken from the nonwoven fabric, the masses were measured, and the average value was converted into the mass per unit area.
[0051] (3) Bulk density (g / cm 3 ) Using a Mitutoyo digital thickness meter, measurements were taken at 30 random locations on the nonwoven fabric, excluding 5 cm at each end, and the average of the measurements was calculated to determine the thickness. The bulk density was calculated from this thickness and the basis weight calculated in (2) using the following formula. Bulk density (g / cm 3 )=Weight (g / m 2 ) / Thickness(mm) / 1000
[0052] (4) MFR (g / 10 min) Using a melt indexer (TOYO SEIKI CO., LTD.: MELT INDEXER S-101) melt flow rate device, the amount of molten polymer discharged per 10 minutes (g) was calculated from the time required to discharge a certain volume of thermoplastic resin under the conditions of JIS-K7210 "Test method for melt mass flow rate (MFR) and melt volume flow rate (MVR) of plastics-thermoplastics" with an orifice diameter of 2.095 mm, an orifice length of 0.8 mm, a load of 2160 g, and a measurement temperature of 230°C.
[0053] (5) Bending stiffness (mm) (flexibility) Measurements were performed according to the 45° cantilever method of JIS-L1096. Five test pieces, 20 mm wide and 150 mm long, were randomly taken from the nonwoven fabric sample in both the vertical and horizontal directions, and placed on a smooth horizontal table with a 45° inclined surface at one end, with the short side of the test piece aligned with the scale baseline. Next, the test piece was gently slid in the direction of the inclined surface, and the position of the other end of the test piece when the center point of one end of the test piece contacted the inclined surface was measured on the scale. The length (mm) traveled by the test piece was measured on the front and back of each of the five pieces, and the average of these values was determined as the bending stiffness.
[0054] (6) Breaking strength (N / 5cm) According to JIS L-1906, five samples were cut out, each 5 cm in length in the CD and 20 cm in length in the MD, and measured with a tensile tester at a gripping distance of 10 cm and a pulling speed of 30 cm / min. The five samples in each longitudinal direction were measured, and the measured values were averaged to calculate the breaking strength.
[0055] (7) Vertical tear strength (N / (g / m 2 )) After removing 5 cm from both ends of the sample, three samples of 10 cm width and 6.5 cm length were cut out, and the longitudinal tear strength (N) was measured using an Elmendorf tear tester to obtain an average value. This was then divided by the basis weight to calculate the tear strength.
[0056] (8) Slittability In the slitting process of the nonwoven fabric manufacturing process, nonwoven fabrics in which the ends were not disturbed and could be cut straight were marked with "O", nonwoven fabrics in which the ends were slightly disturbed were marked with "△", and nonwoven fabrics in which the ends were disturbed or could not be cut were marked with "X".
[0057] Example 1 The first component was polypropylene (PP) resin with MFR of 55g / 10min and melting point of 160℃, and the second component was linear low-density polyethylene (LLDPE) resin with MFR of 40g / 10min and melting point of 130℃. The first component had a discharge rate of 0.4g / min·hole, the second component had a discharge rate of 0.4g / min·hole, and the total single-hole discharge rate was 0.8g / min·hole. Side-by-side type fibers with a mass ratio of the first component to the second component of 50 / 50 were extruded from a spinning nozzle with a nozzle diameter of 0.6mm at a spinning temperature of 230℃ by the spunbond method. The filament group was pulled and extruded toward a moving collecting surface at a spinning speed of 4000m / min to form a side-by-side type long-fiber nonwoven web with an average single fiber fineness of 2.0dtex. The resulting nonwoven web was then subjected to a first hot air air-through treatment at a hot air temperature of 120°C and a hot air speed of 1.0 m / s, then passed between a flat roll and an embossing roll (pattern specification: diameter 0.5 mm, staggered arrangement, horizontal pitch 2 mm, vertical pitch 2 mm, compression area ratio 6.3%) to be thermal embossed at a temperature of 130°C for a heat treatment time of 0.5 ms, and then to a second hot air air-through treatment at a hot air temperature of 130°C and a hot air speed of 1.0 m / s to obtain a web with a basis weight of 20 g / m 2 The physical properties of the obtained long-fiber nonwoven fabric are shown in Table 1 below.
[0058] Example 2 A long-fiber nonwoven fabric was obtained in the same manner as in Example 1, except that the same PP as in Example 1 was used alone to form a fiber containing only PP instead of a side-by-side type fiber, and the temperatures during the hot air air-through treatment and the hot embossing process were each increased by 30° C. The physical properties of the obtained long-fiber nonwoven fabric are shown in Table 1 below.
[0059] Example 3 A long-fiber nonwoven fabric was obtained in the same manner as in Example 1, except that the same LLDPE as in Example 1 was used alone to form a fiber containing only PE rather than a side-by-side type fiber. The physical properties of the obtained long-fiber nonwoven fabric are shown in Table 1 below.
[0060] Comparative Example 1 Except for not carrying out the first and second hot air through treatments, a long-fiber nonwoven fabric was obtained in the same manner as in Example 1. The physical properties of the obtained long-fiber nonwoven fabric are shown in Table 1 below.
[0061] Comparative Example 2 Except for not carrying out the heat embossing process, a long-fiber nonwoven fabric was obtained in the same manner as in Example 1. The physical properties of the obtained long-fiber nonwoven fabric are shown in Table 1 below.
[0062] Comparative Example 3 Except for not carrying out the second hot air air-through treatment, a long-fiber nonwoven fabric was obtained in the same manner as in Example 1. The physical properties of the obtained long-fiber nonwoven fabric are shown in Table 1 below.
[0063] Comparative Example 4 Except for not carrying out the first hot air air-through treatment, a long-fiber nonwoven fabric was obtained in the same manner as in Example 1. The physical properties of the obtained long-fiber nonwoven fabric are shown in Table 1 below.
[0064] [Table 1] [Industrial Applicability]
[0065] The nonwoven fabric according to the present invention has high bulk and breaking strength with cushioning softness, and also has good slittability, and therefore can be suitably used as components of absorbent articles such as disposable diapers, sanitary napkins, and incontinence pads, for example, top sheets, back sheets, and side gathers of disposable diapers.
Claims
1. A nonwoven fabric containing a thermoplastic resin, which has embossed and non-embossed sections, in which the intersections of fibers in the non-embossed sections are melted and bonded, and the value of the longitudinal tear strength of the nonwoven fabric divided by the basis weight is 0.4 N / (g / m 2 ) or less, and the bulk density of the nonwoven fabric is 0.02 g / cm 3 0.09g / cm or more 3 A nonwoven fabric, characterized in that:
2. The nonwoven fabric according to claim 1 , wherein the thermoplastic resin comprises a polyolefin.
3. 3. The nonwoven fabric according to claim 1 or 2, comprising only polypropylene or polyethylene as the thermoplastic resin.
4. 3. The nonwoven fabric according to claim 1, wherein the thermoplastic resin comprises a composite fiber of polypropylene and polyethylene.
5. 5. The nonwoven fabric according to claim 4, wherein the bicomponent fiber is a side-by-side type, a sheath-core type, or an eccentric-core-sheath type fiber.
6. 3. The nonwoven fabric according to claim 1 or 2, which is a long-fiber nonwoven fabric.
7. An absorbent article comprising the nonwoven fabric according to claim 1 or 2.
8. The absorbent article according to claim 7, which is a disposable diaper, a sanitary napkin or an incontinence pad.
9. The following steps: First hot air through treatment step; A hot embossing process; and Second hot air through treatment step; The method for producing a nonwoven fabric according to claim 1 or 2, comprising the steps of:
Citation Information
Patent Citations
JP1975008805A